Efficacy of 1st-line bismuth-containing quadruple therapies with levofloxacin or clarithromycin for the eradication of Helicobacter pylori infection: A 1-week, open-label, randomized trial. Issue 7 (February 2017) - Su, Jing; Zhou, Xiaoying; Chen, Han; Hao, Bo; Zhang, Weifeng; Zhang, Guoxin
Abstract: Background: The aim of the present open-label, randomized control trial was to determine the clinical efficacy and safety of two 1-week bismuth-containing quadruple regimens and 1 levofloxacin-based triple regimen for the eradication of Helicobacter pylori infection in treatment-naive patients. The influence of susceptibility and host CYP2C19 polymorphisms on the efficacy was also evaluated. Methods: Eligible patients were randomly to receive esomeprazole and colloidal bismuth pectin along with clarithromycin and amoxicillin (EBCA), esomeprazole and colloidal bismuth pectin along with levofloxacin and amoxicillin (EBLA), or esomeprazole along levofloxacin and amoxicillin (ELA) for 1 week. The primary outcome was the eradication rate in the intention-to-treat (ITT) and per-protocol (PP) analyses. Results: Overall, 270 patients were randomized. The eradication rates in the above 3 groups were 80.25%, 89.66%, and 81.93% in PP analysis and 72.22%, 86.66%, and 75.56% in ITT analysis, respectively. The eradication rate of EBLA was significantly higher than that of EBCA ( P  = 0.016) in ITT analysis. No significant differences were found among these groups in terms of adverse effects and compliance. The efficacy was significantly affected by levofloxacin resistance for EBLA ( P  = 0.01) and ELA ( P  = 0.04), but not by polymorphisms of CYP2C19 gene for any of the 3 groups. Conclusion: All 1-week bismuth-containing quadruple therapies and levofloxacin-based triple therapy can obtain an acceptable eradication rate, and levofloxacin-based quadruple regimen exhibits the highest eradication rate. The antibiotic resistant rate of levofloxacin was associated with the eradication rate.